Impact of Glycemic Control on Risk of Mortality and Complications in Trauma Patients. Issue 1 (July 2020) - Rajaei, Mohammad; Bosarge, Patrick L.; Griffin, Russell L.; McGwin, Gerald; Jansen, Jan O.; Kerby, Jeffrey D.
Abstract : ABSTRACT: The impact of diabetes mellitus on outcomes in trauma patients continues to attract interest, but data regarding the impact of longer term glycemic control are still lacking. This study evaluated the effect of long-term glycemic control on outcomes. Trauma patients presenting to the University of Alabama at Birmingham Hospital, between 2011 and 2018, were stratified into 4 groups, based on admission Hemoglobin A1c (HbA1c) level. A Poisson regression with robust error variance was used to estimate risk ratios and associated confidence intervals for the association between HbA1C and specific outcomes. A total of 26, 134 patients were included. Patients without diabetes or excellent glycemic control (ND-EGC) had shorter hospital and ICU stay as well as fewer days on ventilator support. Compared with those with ND-EGC, the renal failure risk was higher for those with moderate (risk ratio [RR] 2.53, 95% confidence interval [CI] 1.76–3.63) and poor glycemic control (RR 3.20, 95% CI 2.18–4.71). Urinary tract infection risk was also higher for those with poor control (RR 1.83, 95% CI 1.17–2.02). Observed associations were of similar strength for pneumonia and mortality for all less-than-excellent glycemic control groups. In conclusion, trauma patients with worse long-term glycemic control had increased risks of developing pneumonia, renal failure, urinary tract infection, and death. HbA1c can prognosticate the risks and outcomes of diabetic trauma patients.